Performance assessment and optimization of a solar cooling system to satisfy renewable energy ratio (RER) requirements in multi-family buildings. (August 2020) - Bilardo, Matteo; Ferrara, Maria; Fabrizio, Enrico
Abstract: In order to meet European targets for decarbonisation in 2050, the amount of building energy needs that must be covered through RES is going to increase. Considering the increasing needs for space cooling, mainly due to climate change, technical solutions involving renewable sources of energy for cooling purposes are of great interest. Solar absorption chillers represent a valid answer, but their use in the residential sector is at early stage. This work explores the ability of a solar cooling system to meet the summer energy demand of a multi-family building located in the Mediterranean area. An energy model was developed in TRNSYS® and a simulation-based optimization framework was used to optimize the system design, maximize its energy benefits and relate energy performance to investment and operational costs. The resulting optimal design has reduced the initial non-renewable primary energy demand by 48%, increasing the renewable energy ratio up to 83%. Results demonstrate the ability of the proposed approach to support valuable design choices in this field and reveal the potential of solar cooling to reach the NZEB target in view of future climate change and the future developments of energy requirements for buildings. Highlights: Simulation model of a solar cooling system for multi-family residential building. KPIs definition to implement a simulation-based system optimization. Effective tool to support designers for the optimal exploitation of solar cooling. High renewable energy ratios (up to 83%) are reachable towards future NZEB targets. New policy developments are necessary to improve economic feasibility.